2000
DOI: 10.1021/jp992068a
|View full text |Cite
|
Sign up to set email alerts
|

Water and Methanol Adsorption on MgO(100)/Mo(100) Studied by Electron Spectroscopies and Thermal Programmed Desorption

Abstract: The adsorption of methanol (CH 3 OH) and water (D 2 O) on the MgO(100)/Mo(100) surface at 100 K has been studied by metastable impact electron spectroscopy (MIES), ultraviolet photoelectron spectroscopy (UPS (HeI)), and temperature programmed desorption (TPD). To acquire detailed information regarding the initial stages of adsorption, TPD data, providing information about the relative surface coverage and the molecule-surface interaction, are compared directly with MIES data, which provide information about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
45
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 38 publications
7
45
2
Order By: Relevance
“…Depending on the experimental conditions, the existence of the surface healing dissociation mechanism may prevent the hydroxyl group from being detected by experiments such as in Goodman and co-workerss experiments. [31,32] The possibility for hydrogen formation and surface healing upon dissociation of a water molecule on an oxygen vacancy was first suggested by Finocchi et al [7] However, the mechanism for such a process was found to be very different in our study. In the study by Finocchi et al, hydrogen formation is from the product of the normal dissociation pathway N P in which hydrogen formation occurs by abstraction of the hydrogen atom in OH along with the hydrogen in the vacancy.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…Depending on the experimental conditions, the existence of the surface healing dissociation mechanism may prevent the hydroxyl group from being detected by experiments such as in Goodman and co-workerss experiments. [31,32] The possibility for hydrogen formation and surface healing upon dissociation of a water molecule on an oxygen vacancy was first suggested by Finocchi et al [7] However, the mechanism for such a process was found to be very different in our study. In the study by Finocchi et al, hydrogen formation is from the product of the normal dissociation pathway N P in which hydrogen formation occurs by abstraction of the hydrogen atom in OH along with the hydrogen in the vacancy.…”
contrasting
confidence: 52%
“…[30][31][32] Therefore, the experimental detection of hydroxy groups exhibits a strong dependence on the measurement conditions as well as on the surface preparation, demonstrating the complex mechanisms of water dissociation on surface defects. [22,[31][32][33][34] The ambiguity regarding the mechanism of water dissociation on the defective MgO surfaces still persists. [35] The adsorption of a water molecule on a defective MgO surface has also been examined in a number of theoretical studies.…”
mentioning
confidence: 99%
“…However, a strong dependence of desorption energy on substrate material is expected. A desorption energy of 632 meV for water on MgO(1 0 0) surface has been reported by Günster et al (2000).…”
Section: Methodsmentioning
confidence: 94%
“…This is because only the (slower) Auger Deexcitation (AD) mechanism is occurring on the insulating MgO whereas the metal surfaces allow for Resonant Transfer (RT) with the conducting surface (see sec. 2.2.3) states strongly influencing the peak shape and intensity of the MIE spectra [173,246,323]. 10 As visible from tab.…”
Section: Tce -Adsorption Properties On Surfacesmentioning
confidence: 93%
“…As seen in fig. 4.4.3, the second O2p feature at a BE of 9.1 eV corresponding to O2p (MOs parallel to the surface plane) is less suitable as it is visible exclusively in UPS [245,323] at coverages below 0.15 TCE /SA. For MIES the TCE features are detected after dosage of an equivalent amount of 0.02 TCE /SA, while the sensitivity in UPS is greatly reduced (to 0.4 TCE /SA) due to the overlap with the O2p features of the oxide support.…”
Section: Tce -Adsorption Properties On Surfacesmentioning
confidence: 99%